What determines value? Exploring value characteristics of novel therapies for digestive system cancers - Ou, Shunlong; Wang, Song; Chen, Xiaoyi; Li, Huan; Zhou, Chengyang; Jiang, Qian (Frontiers in Immunology, 2026)
IntroductionDespite the growing arsenal of novel anti-tumor drugs for digestive system cancers, concerns persist regarding their true clinical value, as approvals often rely on surrogate endpoints with limited overall survival or quality of life data. This study systematically evaluates the clinical benefit of these drugs in China using standardized value assessment frameworks and identify factors associated with high-value treatments.MethodsThis cross-sectional study analyzed 65 indications from 33 novel anti-tumor drugs included in the Guidelines for the Clinical Application of Novel Anti-tumor Drugs for advanced digestive system cancers. Two researchers independently extracted data from drug approval documents and PubMed literature. Value assessment was performed using ASCO Value Framework v2.0 (advanced disease) and ESMO-Magnitude of Clinical Benefit Scale v2.0 (non-curative). For ASCO-VF, the net health benefit score was calculated based on clinical benefit, toxicity adjustments, and bonus points. ESMO-MCBS grading incorporated clinical benefit magnitude with adjustments for toxicity and quality of life. Statistical analyses included descriptive statistics and association testing with odds ratios for categorical variables.ResultsAmong 65 indications, only 12 (18.5%) achieved value thresholds in both frameworks. Immune combinations showed superior value, particularly atezolizumab-bevacizumab in hepatocellular carcinoma (ASCO-VF: 53.4; ESMO-MCBS: grade 5) and toripalimab in esophageal squamous cell carcinoma. Quality of life improvement strongly correlated with value attainment in both frameworks (ASCO-VF OR: 28.00; ESMO-MCBS OR: 27.87). Molecular target detection requirement inversely associated with OS benefit (OR: 0.16). Value heterogeneity was observed across cancer types and treatment lines.ConclusionsFew novel digestive system cancer drugs demonstrate substantial clinical benefit in both value frameworks. Quality of life documentation is crucial for value assessment. Stakeholders should integrate these value dimensions—survival benefit, toxicity, and quality of life—into clinical and policy decisions to guide treatment selection and resource allocation.